Learning arabic through multimedia / Junainah Mohamad - Mohamad, Junainah (2002)
The existing of new technology makes life become easier. Learning process also has changed to make it easier and interesting. Computer as a tool in education field is become popular technique. This project used the multimedia tools to teach children Arabic language. This project developed to supplement the pre-school curriculum especially Islamic kindergarten that teaches Arabic language as one of their important subject. The target users for this project are for children at ages 4 to 6 years old. This program introduces the student to alphabets, face of human, numbers and colours in Arabic. There are also exercises included to test how far the students understand what are they had learned. The exercise such as completes the Arabic letters, suit the object with the right word, colour the alphabet and read the short sentence. There is also a funsite where the students can play a simple game as an additional activity. The program is presented in colourful screen include animated picture, movie and sound that will be beneficial to the children to learn this language.